ICPSR Instructional Subset: Justifying Violence: Attitudes of American Men, 1969 - Blumenthal, Monica D. ([Verlag nicht ermittelbar], 1984)
This survey of attitudes of 1,374 American men aged 16-64 toward violence was conducted in the summer of 1969 by the Survey Research Center of the Institute for Social Research at the University of Michigan. The investigators examined the level of violence that respondents viewed as justified to accomplish social control and social change and also probed the respondents' personal values, their definition of violence, and their identification with groups involved in violence. To examine the degree of violence that American men felt could be justified for social control, the investigators asked respondents to react to situations involving protests and other disturbances. These situations included hoodlum gang disturbances, student protests, and Black protest demonstrations. The respondents were asked what police actions from "letting it go" to "shooting to kill" were appropriate as police control measures. Several such items were combined to form an index of "violence for social control." In questions dealing with the level of violence necessary to bring about social change, respondents were asked if they agreed with the necessity of "protest in which some people will be killed" in order to bring about changes sought by Blacks, by student demonstrators, and in general. These items were combined into an index of "violence for social change." This instructional subset from the original study also includes an initial series of questions that asked whether respondents viewed such actions as protest demonstrations, police frisking, looting, burglary, and draft-card burning as violence. This was followed by inquiries into the possible causes of violence and motives of those who participate in violence. Another set of variables deals with respondents' relative views of property damage and personal injury and their opinions on the use of violence to prevent violence, violence as a teaching tool, forgiveness of one's attacker, and the roles of courts and police agencies in combating crime. The subset concludes with a number of derived indices of violence attitudes that drew upon survey questions to form general patterns. These derived indices include retributive justice, self-defense, humanism, property-person priority, kindness, police-court power, court fairness, social causes, trust, and peer consensus indices. Finally, several summary measures gauge the respondents' general approval of violence for social control and social change purposes. Demographic variables specify education, age, religion, socioeconomic status, and region of the country.